Parenting styles as predictors of executive function in children aged 5 to 6 years in Hulu Langat, Selangor, Malaysia - Mohan, Sindhu; Mamat @ Mukhtar, Firdaus; Imran, Haris Murad (Faculty of Human Ecology, Universiti Putra Malaysia (UPM), 2024)
Background Executive functions (EF) are a set of skills that develop from childhood and are vital in predicting future success. As these skills develop rapidly between the ages of three to five years old, parents play a crucial role in ensuring that a proper framework is set to support its development in their children. One parental factor that contributes to the development is parenting style. Hence, the aim of this study is to investigate the role of parenting styles on EF function in preschool children. Methods One hundred and forty-one parents and children between 5 and 6 years old (M = 5.46, SD = 0.5) from the Hulu Langat district of Selangor participated in this study. This cross-sectional study used the Behaviour Rating Inventory of Executive Function—Preschool Version (BRIEF-P) to measure EF while the Parenting Style Four Factor Questionnaire (PS-FFQ) was used to determine parenting styles. The questionnaires were completed by the main caregiver of these children. Results Findings suggest an authoritative parenting style had a significant positive relationship with EF while the uninvolved parenting style would negatively affect the development of a child’s EF. On the other hand the regression analysis showed that, the authoritative and authoritarian parenting were both significant predictors of EF. Conclusions This study showed that of the different parenting styles, the authoritative parenting style had a good relationship with EF which indicated that this parenting style would contribute to the healthy development of EF in preschool children which in turn would contribute to the development of competent adults.